2011
DOI: 10.1111/j.1399-3046.2011.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple extramedullary relapses without bone marrow involvement after second allogeneic hematopoietic stem cell transplantation for acute myeloid leukemia

Abstract: EMR without BM involvement after allogeneic HSCT is extremely rare, especially in children; only a few cases have been reported. A two-yr-old boy was diagnosed with AML (M4) and underwent allogeneic HSCT in first complete remission with BM from HLA-matched unrelated donor without GVHD. Four yr later, he had a BM relapse and after induction and consolidation chemotherapy, he received a second HSCT from an unrelated donor using peripheral blood stem cells. His second post-transplant course was complicated by ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In 15-35% of cases, MS can appear concomitantly with AML, whereas, in 50% of cases MS appears following the diagnosis of AML. In rare instances (<1%), MS has also been diagnosed after allogenic stem cell transplantation (allo-SCT), which manifests as an isolated tumor with or without accompanying blood and bone marrow relapse [14,15].…”
Section: Epidemiologymentioning
confidence: 99%
“…In 15-35% of cases, MS can appear concomitantly with AML, whereas, in 50% of cases MS appears following the diagnosis of AML. In rare instances (<1%), MS has also been diagnosed after allogenic stem cell transplantation (allo-SCT), which manifests as an isolated tumor with or without accompanying blood and bone marrow relapse [14,15].…”
Section: Epidemiologymentioning
confidence: 99%
“…Extramedullary relapse is an important complication, which is more frequent in post-transplant patients compared with patients treated without alloHSCT. Its incidence is about 7–46% of all AML relapses [ 18 ]. It may occur with or without bone marrow involvement, but isolated extramedullary relapse rarely occurs; in children it is limited to case reports [ 4 , 18 ].…”
Section: Clinical Manifestation Of Myeloid Sarcomamentioning
confidence: 99%
“…Thus, the diagnosis of an EM relapse is often delayed until patients develop the symptoms of a large mass, such as abdominal pain or constipation. However, a number of recent reports have shown that EM infiltration of AML can be detected by 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) or FDG-PET/computed tomography (CT) [43][44][45][46][47][48][49][50][51][52][53]. St€ olzel et al [54] recently reported the results of FDG-PET/CT in 10 patients with AML with histologically proven EM disease at diagnosis (n 5 5), relapse after alloSCT (n 5 4), or relapse after chemotherapy (n 5 1).…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%